Ukraine : Request for A Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2014)
This paper discusses Ukraine's Request for a Stand-by Arrangement. Ukraine's economy had been in recession since mid-2012. Inconsistent macroeconomic policies pursued in 2012-2013 aggravated deep-seated vulnerabilities and eventually generated a balance-of-payment crisis. Key objectives of the authorities' program are to restore macroeconomic stability, strengthen economic governance and transparency, and lay the foundation for robust and balanced economic growth. To achieve these objectives, the government will implement immediate measures aimed at securing stability, combined with deeper reforms to achieve and sustain external sustainability, ensure financial stability, restore sound public finances, rationalize the energy sector, and improve the business environment.